Multicultural Influence of the Conceptual Value of Civilization on Changes in Islamic Law - Zulbaidah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Islamic law moves with the times, Islam does not deny ijtihad as a solution offered in the formation of Islamic law. This study aims to analyze that Islamic Law is inseparable from the conceptual values of civilization, where different laws do not have to be prohibited, so that the relationship of Islamic law with diverse cultures is not a rigid law but can change according to changes and human welfare at a certain time. Descriptive analysis became the method used in this study. This study concludes that, first: Culture is an important concept in understanding society, where culture has three layers, namely: basic values that can be maintained, behaviors consisting of rituals and certain symbols. Second, Islamic law is a dynamic and flexible law, where attention to this change is then used as one of the important reasons in extracting law by scholars in conducting ijtihad, because many laws change according to social and cultural changes while still paying attention to the demands of benefit, not about mahdhah worship, the law is not qath'i, and that change must be based on the proposition of shari'i.